Psychromonas Aquatilis Sp. Nov., Isolated from Seawater Samples Obtained in the Chilean Antarctica - Cortez-San Martin, M (Microbiology Society, 2017)
A slightly beige-white pigmented, Gram-staining-negative, rod-shaped bacterium, strain M1A1T, was isolated from seawater samples obtained in Fildes Bay, Antarctica (62°12′ S 58° 57′ W). Phylogenetic analysis based on nearly full-length 16S rRNA gene sequences showed that the isolate shared 98.4% 16S rRNA gene sequence identity to the type strain of Psychromonas arctica, but less than 97% 16S rRNA gene sequence similarities to all other species of the genus Psychromonas. DNA–DNA hybridization with Psychromonas arctica DSM 14288T showed low values (21%, reciprocal 27%). The main cellular fatty acid of strain M1A1T was summed feature 3 fatty acids (C16: 1ω7c/C16: 1ω8c), followed by C16: 0. Based on phylogenetic, chemotaxonomic, genomic and phenotypic analyses, we propose a novel species of the genus Psychromonas with the name Psychromonas aquatilis sp. nov. and the strain M1A1T (=CIP 111183T=CCM 8710T=LMG 29766T) as type strain. © 2017 IUMS.